Effects of dietary supplementation with dandelion tannins or soybean isoflavones on growth performance, antioxidant function, intestinal morphology, and microbiota composition in Wenchang chickens - Li, Xiang; Sun, Ruiping; Liu, Quanwei; Gong, Yuanfang; Ou, Yangkun; Qi, Qi; Xie, Yali; Wang, Xiuping; Hu, Chenjun; Jiang, Shouqun; Zhao, Guiping; Wei, Limin (Frontiers in Veterinary Science, 2023)
This study investigated the effects of dietary supplementation with dandelion tannins or soybean isoflavones on growth performance, antioxidant capacity, and intestinal health of female Wenchang chickens. A total of 300 chickens were randomly divided into 5 groups with 6 replicates and 10 for each replicate. The control group (Con) were fed basal diet; the 4 experimental groups were fed a basal diet with different supplements: 300 mg/kg Dandelion tannin (DT1), 500 mg/kg Dandelion tannin (DT2), 300 mg/kg Soybean isoflavone (SI1), or 500 mg/kg Soybean isoflavone (SI2). The experiment lasted for 40 days. Results showed that the final body weight and average daily gain were higher in the DT2 and SI1 groups than in the Con group (P < 0.05). In addition, the experimental groups increased the level of serum albumin (P <0.05); the concentrations of serum aspartate aminotransferase and glucose in SI1 group were significantly increased (P < 0.05) compared to the Con group, as well as the concentration of triglycerides in DT1 group (P < 0.05). Compared to the control group, the DT1 or SI1 group was high in the CAT level in serum (P < 0.05). The DT2 or SI1 group was lower than the Con group in the ileum pH value (P < 0.05). Moreover, the jejunum villus height and mucosal muscularis thickness were increased in DT2 and SI1 groups (P < 0.05), and the jejunum crypt depth in DT1 or DT2 group was decreased (P < 0.05) when compared to the Con group. In addition, the mRNA expression level of ZO-1 in the duodenum in SI1 group and that of occludin, ZO-1, and claudin-1 in the ileum in DT2 and SI1 groups were upregulated（P < 0.05).The DT2 and SI1 groups decreased Simpson and Shannon indices relative to the control. The relative abundance of Proteobacteria was lower and that of Barnesiella was higher in DT2 group (P < 0.05) than in Con group. Overall, dietary supplementation with 500 mg/kg dandelion tannins or 300 mg/kg soybean isoflavones improved the growth performance, serum biochemical indexes, antioxidant function, intestinal morphology, and modulated the cecal microbiota of Wenchang chickens.